Crescimento inicial de espécies arbóreas nativas da Mata Atlântica em resposta ao controle de espécies indesejáveis e a fertilização mineral - Ornelas, Adélia Carla Santos (2021)
Interventions in ecological restoration are very varied and the success of global efforts to implement it on a large scale depends on the capacity to develop and improve effective techniques and guidelines. Studying how silvicultural practices impact the growth of trees in forest restoration plantations is relevant, since the adoption of such practices can impact the ecological and economic aspects of forest restoration. We tested the hypothesis that native tree seedlings respond positively to the intensification of fertilization and weed control, even in areas of intensive agriculture with recurrent fertilization and chemical weed control before restoration planting. We carried out the study in Araras-SP, with 22 species of native trees, of which 11 are classified as fast-growing and wide canopy species (hereafter referred to as shade species), and the other 11 were species not classified as fast-growing or wide canopy species (hereafter referred to as diversity species), in an area previously destined for decades to intensive agriculture and with good levels of soil fertility for planting native trees. The experimental was completely randomized in a split-plot design, with 24 plots and four treatments: 1 - intensive weed control with fertilization; 2 - intensive weed control without fertilization; 3 - non-intensive weed control with fertilization; and 4 - non-intensive weed control without fertilization. In addition to the mowing of the seedlings, in intensive control there was application of glyphosate-based herbicide every three months and in non-intensive mechanized mowing every six months, both between rows. Fertilization carried out was with NPK in three moments, we applied 53 kg ha-1 of N, 35 kg ha-1 of P and 51 kg ha-1 of K. We evaluated the basal diameter at the ground level, the total tree height, and the crown projection area, in three distinct periods, four, 10 and 16 months after planting. We submitted the results to analysis using a generalized linear model and a post hoc test (Emmeans) to assess significant differences (p < 0.05). Individually, the planting group and the species influence of all growth variables investigated, fertilization only influenced the increase in basal diameter and the method of weed control did not influence any of the measured variables. The interaction between the weed control and tree species influenced the three variables, the fertilization with planting group influenced the height increase and the fertilization interaction with the species influenced the increases in basal diameter and height. In general, shade species showed greater growth than those in the diversity species group, but this growth was variable when we looked at the tree species and not all shade species showed greater increments than the diversity species. Although forest intensification is generally an advantageous practice for tropical forest restoration plantations, our results show that in an area previously used for intensive agriculture, its benefits at 16 months are not remarkable. Thus, both local and historical factors must be incorporated in the decision to intensify forestry in forest restoration.